Competitive strategies in the digital age : the case of small electronic firms in Greece - Georganta, Zoi; Vogiaji, Margarita (SPOUDAI Journal of Economics and Business, 2009)
The purpose of this paper is twofold: First, to investigate whether Porter’s generic strategies are also followed inthe digital age; second, to test econometrically whether strategic planning affects positively the performance of electronic firms. To achieve its purpose, the paper uses the structural analysis of latent variable models.The data comes from semi-structured interviews and a questionnaire survey of 2,500 e-firms in Greece. The maximum likelihood estimates of the model indicate, first, the validity of Porter’s generic strategies in today’s digital economy and, second, a strong dynamic relationship between strategic planning and economic performance of e-businesses operating in Greece. The findings are in agreement with previous empirical work. JEL Classifications: M21, C51